MAKING AID AGENCIES WORK : reconnecting ingos with the people they serve. - GIBSON, TERRY (EMERALD Group PUBL, 2019)
Terry Gibson combines large-scale industry analysis with attention to the lives and worlds of the people the aid industry aims to serve, and he demonstrates how to overcome barriers between the two worlds and free flows of learning, resources, and even political influences that might lead to better outcomes.